Effect of Mechanical Horse Practice as New Postural Training in Patients With Neurological Disorders: A Pilot Study - Baillet, Héloïse; Leroy, David; Vérin, Eric; Delpouve, Claire; Benguigui, Nicolas; Komar, John; Thouvarecq, Régis (Frontiers in Psychology, 2019)
Objective From a dynamic system approach, this study evaluated the impact of a new training protocol using a mechanical horse on the postural coordination of brain-damaged patients. Methods Eighteen volunteer brain-damaged patients (i.e., post-stroke or traumatic brain injury) were recruited and randomly divided into an experimental group (horse group; n=10, conventional therapy associated with horse-riding exercise on the mechanical horse for 30 minutes, twice a week, for 12 weeks) and a control group (n=8; conventional therapy without intervention on the mechanical horse). Postural coordination was evaluated during pre- and post-tests through discrete relative phase (DRP) computation: ϕHead-Horse, ϕTrunk-Horse. Results A significant effect of used training has been showed, F(1,15)=16.6 (p<.05) for all patients, concerning the trunk/horse coordination. Conclusion This pilot study results showed the impact of this new training method on the postural coordination of these patients. After 24 sessions, the coordination of the horse group patients differed from that of the control group, showing their ability to adapt to constraints and develop specific modes of postural coordination (trunk/horse antiphase) to optimize their posture.